AB0311 THE PROPER STUDY: RESULTS OF THE FIRST INTERIM ANALYSIS OF A PAN-EU REAL-WORLD STUDY OF SB5 BIOSIMILAR FOLLOWING TRANSITION FROM REFERENCE ADALIMUMAB IN PATIENTS WITH RHEUMATOID ARTHRITIS, AXIAL SPONDYLOARTHRITIS OR PSORIATIC ARTHRITIS. (2nd June 2020) - Müller-Ladner, U.; Gaffney, K.; Jadon, D.; Freudensprung, U.; Addison, J.
Abstract : Background: SB5, a biosimilar to reference adalimumab (ADA), received EU marketing authorisation in August 2017, based on the totality of evidence from pre-clinical and clinical Phase I and III studies that demonstrated bioequivalence, similar efficacy, and comparable safety and immunogenicity to the reference. There are few published data on the transition from reference to biosimilar ADA outside the controlled, randomised, clinical trial setting. Objectives: To evaluate candidate predictors of persistence on SB5 in EU patients across multiple indications. Methods: This ongoing observational study will enrol approximately 1200 subjects with rheumatoid arthritis (RA), axial spondyloarthritis (axSpA) or psoriatic arthritis (PsA), who initiated SB5 as part of routine clinical practice following a minimum of 16 weeks' treatment with reference ADA, at clinics in Belgium, Germany, Ireland, Italy, Spain and the UK. Data are captured from clinic records retrospectively for the 24 weeks prior to transition, and prospectively and/or retrospectively for 48 weeks following transition. The primary objective is to evaluate candidate predictors of persistence, and primary outcome measures include baseline clinical characteristics, disease activity scores, clinical management and patient satisfaction over time. This interim analysis provides an overview of baseline characteristics for subjects enrolled and followed up by the data extract date of 20 th December 2019. Results: Of the 123 patients included in this interim analysis, 43 suffer from RA, 42 from axSpA and 38 from PsA. Conclusion: This interim analysis provides a first insight into a contemporary cohort of EU patients with established RA, axSpA and PsA, switched from reference to biosimilar ADA in clinical practice. The majority of patients have stable disease at transition, 85% or more of each cohort transitioned to the same dose regimen of biosimilar as received for the reference prior to transition, and most are aware of correct storage and self-administration of their biosimilar medication. With ongoing enrolment and longer follow-up, the study will provide pertinent information about clinical outcomes of transition from reference to biosimilar adalimumab in real-world practice and in indications not investigated in controlled studies. Disclosure of Interests: Ulf Müller-Ladner Speakers bureau: Biogen, Karl Gaffney Grant/research support from: AbbVie, Celgene, MSD, Novartis, Pfizer, and UCB Pharma, Consultant of: AbbVie, Celgene, MSD, Novartis, Pfizer, and UCB Pharma, Speakers bureau: AbbVie, Celgene, MSD, Novartis, Pfizer, and UCB Pharma, Deepak Jadon: None declared, Ulrich Freudensprung Shareholder of: Biogen International GmbH, Employee of: Biogen International GmbH, Janet Addison Shareholder of: Biogen Idec, Employee of: Biogen Idec